Self-Motivation vs Previous Grades as Predictors of Success in Counsellor Training - Sharpley, Christopher F.; Pain, Michelle D. (Canadian Journal of Counselling and Psychotherapy, 2011)
The prediction of academic success at the graduate level is a major issue for educators. While some previous research has suggested that undergraduate GPA is a valid predictor, other data contradict this finding. Of particular relevance for graduate programs in counselling psychology, the selection of students who are most likely to successfully learn the theory and skills necessary to help others remains open to investigation. As an alternative to some previous research which has focused upon personality attributes, the present study compares level of self-motivation as measured by questionnaire to previous grades in psychology and non-psychology courses as predictor variables of success in an introductory counsellor training course. Written, practical, and combined assessments of students in the course were used as the criterion variables in a regression analysis which revealed that motivation to succeed was the most effective predictor variable. Issues are raised for discussion regarding the reliable selection of students to undertake counsellor training.